An Outlook on COVID-19 with Homoeopathic Perspective (Homoeopathy for All, 2022)
Corona virus disease 2019 is an  infectious disease caused by severe  acute respiratory syndrome corona  virus 2 (SARS-CoV-2). This is  firstly reported in December 2019  in Wuhan city of China and now  this pandemic has become a global  public health problem. Many  people infected with COVID-19  virus may remain asymptomatic  and some may experience mild to  moderate respiratory illness. Many  of them recover without any specific  treatment, but older people and  those with other medical problems  like cardiovascular disease, chronic  respiratory disease and diabetes  are more prone to develop serious  illness. Till now many therapies were  developed for the treatment of covid  19 virus. Still vaccines and effective  remedies are on development which  are time consuming process because  it needs pre clinical to clinical trials.  So now it becomes essential to  introduce the utility of alternative  treatments such as of Ayurveda,  Siddha, Homoeopathy or Unani.  These ancient modes of treatments  are very efficient and can save lives  of sufferers in less time with less  expenditure. Homoeopathy has  benefitted human kind in epidemics  since over the last centuries. In  epidemic diseases, each case should  be treated as a fresh one and studied  thoroughly. After studying a number  of patients, physician get to know  about the true state of present  illness and can select a suitable  homoeopathic medicine called  “Genus epidemicus”. This particular  genus epidemicus can provide us  with a safe and effective treatment  in epidemic disease.
Keywords: Corona virus; COVID-19; Genus epidemicus; Homoeopathy